2003
DOI: 10.1289/ehp.5437
|View full text |Cite
|
Sign up to set email alerts
|

Histopathologic and histochemical biomarker responses of Baltic clam, Macoma balthica, to contaminated Sydney Harbour sediment, Nova Scotia, Canada.

Abstract: Sediments in Sydney Harbour, Nova Scotia, are highly contaminated by polynuclear aromatic hydrocarbons (PAHs), polychlorinated biphenyls (PCBs), and heavy metals. Histopathologic and histochemical evaluations were made on the Baltic clam, Macoma balthica, exposed to 11 Sydney Harbour sediment samples. Histologic lesions in digestive gland (tubular dilation or atrophy, macrophage aggregates, tubular cell necrosis, and tissue inflammation) and gonads (macrophage aggregates, supporting cell, germ cell, and ovaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…Enhanced resorption of abnormal and dead germ cells has been reported for different invertebrate species experimentally exposed to toxicants (Maung Myint and Tyler 1982;Cajaraville et al 1990;Au et al 2003;Lehmann et al 2007;Schäfer and Köhler 2009) or inhabiting polluted waters (Syasina et al 1991;Binelli et al 2001;Vaschenko et al 2001;Tay et al 2003; the present study). Our study showed a positive correlation between IPA res and IPA hyp in sea urchins of both sexes (r = 0.81 [p = 0.051] and r = 0.84 [p = 0.038] for female and male sea urchins, respectively).…”
Section: Discussionsupporting
confidence: 65%
“…Enhanced resorption of abnormal and dead germ cells has been reported for different invertebrate species experimentally exposed to toxicants (Maung Myint and Tyler 1982;Cajaraville et al 1990;Au et al 2003;Lehmann et al 2007;Schäfer and Köhler 2009) or inhabiting polluted waters (Syasina et al 1991;Binelli et al 2001;Vaschenko et al 2001;Tay et al 2003; the present study). Our study showed a positive correlation between IPA res and IPA hyp in sea urchins of both sexes (r = 0.81 [p = 0.051] and r = 0.84 [p = 0.038] for female and male sea urchins, respectively).…”
Section: Discussionsupporting
confidence: 65%
“…PAHs and oil are known to increase the prevalence of oocyte atresia in sea urchins (Schäfer and Köhler, 2009) as well as in other invertebrates (e.g., Lowe and Pipe, 1986;Tay et al, 2003;OrtizZarragoitia and Cajaraville, 2006). In the present study, oocyte atresia was not induced by exposure to 5 or even 150 mg phenanthrene L À1 for 10 days, and only exposure to as much as 500 mg L À1 phenanthrene for 20 days increased atresia of previtellogenic oocytes in a previous study (Schäfer and Köhler, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that PAHs and oil elicit histopathological effects on gonads in marine invertebrates such as degeneration of germ cells and gonadal follicles, atrophy of gonadal tissue as well as inflammatory reactions (Lowe and Pipe, 1986;Berthou et al, 1987;Cajaraville et al, 1990;Tay et al, 2003;Aarab et al, 2004;Ortiz-Zarragoitia and Cajaraville, 2006). Indeed, the mentioned studies deal solely with molluscan species.…”
Section: Discussionmentioning
confidence: 99%